Community health status of Banpa Population: the increasing burden of heatlh risks - Laoitthi, Poranee (Chulalongkorn Medical Journal, 2023)
Background : Population health survey is an important tool to better our understand about health situation in community. It allows us to have comprehensive picture of the risks and health outcomes of the population. With good design, it can provide a good representation of community health including some additional dimensions not commonly measured such as social capital. Objective : To understand health outcomes and health risks in the population of Tambon Banpa, Kaeng Khoi district, Saraburi Province. Methods : Cross-sectional survey using cluster two-stage sampling method. Three of 11 villages were randomly selected. In each village, proportionate samples of households with head of household or representative of the household age 18 or over at the time survey were included in the study. A questionnaire was developed. Direct interview of survey respondents was done on June 8, 2016 by fourth year Chulalongkorn University medical students. Results : Overall 235 households were included in the survey. There were 910 people residing in these households: mean age was 40.3 (SD = 22.4), 52.1% were female, 56.7% single family, 61.0% were under the universal healthcare coverage. Top health problems were hypertension with no major mental health issues. Smoking and drinking were less than that of the Thai general population. Overweight and obese were over 60.0% of the respondents. Over 90.0% coverage on EPI and 96% breast feeding and 82.0% were given till 6 months. Majority reported good quality of life score. Happiness index and quality of life (QOL) were correlated. Conclusion : Demographic characteristics in Tambon Banpa revealed a trend towards ageing community with similar prevalence of chronic disease with Thai population. Happiness Index and QOL were relatively good. However, overweight and obese patterns were higher in this population.